Nutrition education in the Australian New South Wales primary school curriculum: An exploration of time allocation, translation and attitudes in a sample of teachers. (29th August 2018) - de Vlieger, Nienke; Riley, Nicholas; Miller, Andrew; Collins, Clare E.; Bucher, Tamara
Abstract: Issue addressed: The dietary intakes of Australian children are not optimal, with few meeting recommended vegetable and fruit intake targets. Nutrition education in childhood is important for developing healthy eating patterns, with schools an ideal setting for a wide reach. The aims of this study were to examine nutrition education within the NSW primary school syllabus, explore how much time teachers spend teaching nutrition, what is taught, what materials are used, and to identify attitudes towards nutrition education. Method: An online survey consisting of 29 closed questions (with options for comments) was specifically developed for the purpose of this study. Teachers currently teaching at a NSW primary school were eligible to participate. Results: A total of 33 NSW primary school teachers completed the survey. Results indicate that limited time is spent on teaching nutrition with some important nutrition education components currently missed, resources perceived to be inadequate and lack of time reported as the largest barrier to teaching nutrition. Conclusion: In order to improve the quality of nutrition education in NSW primary schools, several important topics need to be integrated into the curriculum, and time constraints of teachers should be taken into account. So what?: Findings from the current survey will inform the development of future nutrition education programs and resources with the aim of integrating nutrition education within the primary school curriculum.